2019
DOI: 10.1186/s11658-019-0183-8
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase-A activity is required for clonal tumorsphere formation by human breast tumor cells

Abstract: BackgroundBreast tumor growth and recurrence are driven by an infrequent population of breast tumor-initiating cells (BTIC). We and others have reported that the frequency of BTIC is orders of magnitude higher when breast tumor cells are propagated in vitro as clonal spheres, termed tumorspheres, by comparison to adherent cells. We exploited the latter to screen > 35,000 small molecules to identify agents capable of targeting BTIC. We unexpectedly discovered that selective antagonists of serotonin signaling we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Consequently, MAO-A and MAO-B selective antagonists were evaluated using cell viability and sphere-forming assays. By contrast to our expectations, three selective MAO-A antagonists tested reduced cell viability and the frequency of sphere-forming cells derived from the two breast cancer cell lines (MCF-7 and HCC1954) that were tested [ 57 ]. MAO-B selective antagonists had no effect in the latter assays.…”
Section: Monoamine Oxidase a (Mao-a)contrasting
confidence: 66%
See 3 more Smart Citations
“…Consequently, MAO-A and MAO-B selective antagonists were evaluated using cell viability and sphere-forming assays. By contrast to our expectations, three selective MAO-A antagonists tested reduced cell viability and the frequency of sphere-forming cells derived from the two breast cancer cell lines (MCF-7 and HCC1954) that were tested [ 57 ]. MAO-B selective antagonists had no effect in the latter assays.…”
Section: Monoamine Oxidase a (Mao-a)contrasting
confidence: 66%
“…In advance of performing mechanistic studies with the antagonists, we determined whether MAO-A transcripts and protein were expressed in a panel of 10 human breast tumor cell lines comprising all clinical subtypes. MAO-A was not expressed in the majority of breast tumor cell lines when they were propagated in serum-containing media: however, its abundance at both the RNA and protein levels was dramatically increased when the tumor cells were cultured in chemically defined media as tumorspheres [ 57 ]. Hence, in vitro culture conditions conducive for maintaining a high BTIC frequency stimulates MAO-A expression.…”
Section: Monoamine Oxidase a (Mao-a)mentioning
confidence: 99%
See 2 more Smart Citations
“…We subsequently demonstrated that structurally unrelated selective antagonists of other serotonin pathway components target mouse [17] and human BTIC [18] using multiple orthogonal assays. In short, antagonists of tryptophan hydroxylase 1 (TPH1), monoamine oxidase A (MAO-A), SERT and each of 5 of the 17 5-HTRs inhibited tumorsphere formation by each of six human breast tumor cell lines independent of the breast cancer subtype that they model [18,19]. A highly selective 5-HT5A antagonist (SB-699551) was the most potent of all the compounds tested in these assays.…”
Section: Introductionmentioning
confidence: 99%